2010
DOI: 10.1016/j.psc.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Cognitive Behavioral Therapy for Adult Attention-Deficit Hyperactivity Disorder

Abstract: Synopsis Attention-deficit / hyperactivity disorder (ADHD) is a valid and impairing psychological disorder that persists into adulthood in a majority of cases and is associated with chronic functional impairment and increased rates of comorbidity. Cognitive-behavioral therapy (CBT) approaches for this disorder have emerged relatively recently, and available evidence from open and randomized controlled trials suggests that these approaches are promising in producing significant symptom reduction. A conceptual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 24 publications
0
92
0
1
Order By: Relevance
“…This possibility raises the question of what should be appropriate subjective outcome measures in studies of cognitive training for adults with ADHD. It has been suggested that instead of report of ADHD symptoms, a better measure would be report of the need for compensatory strategies to cope with symptoms (Knouse and Safren 2010). In addition, other objective measures of daily life functioning such as academic performance are important in order to assess the broad impact of any given treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility raises the question of what should be appropriate subjective outcome measures in studies of cognitive training for adults with ADHD. It has been suggested that instead of report of ADHD symptoms, a better measure would be report of the need for compensatory strategies to cope with symptoms (Knouse and Safren 2010). In addition, other objective measures of daily life functioning such as academic performance are important in order to assess the broad impact of any given treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[5,7,11] We concentrated on three areas: preparation, organization and setting priorities, and managing distractions. [8,10] We used retrospective, reflective review of his most recent clinical shifts to prompt WYM's rehearsal and planning for upcoming shifts. WYM was affirmed and commended for implementing actions and strategies which had positive outcomes.…”
Section: Coachingmentioning
confidence: 99%
“…Weekly coaching sessions, using retrospective reflection and review, provided us with a concrete, practical teaching strategy intervention, and helped our student, WYM, to develop lasting clinical executive skills. [5,8,10] A crucial parallel metacoaching intervention supported and encouraged the clinical NI to reinforce the coaching strategies with the student in the clinical practice setting. Throughout all coaching sessions, with the student and meta-coaching of the NI, the expert nurse-coaches focused on increasing the student's self-esteem, belief in own self-efficacy and decreasing performance anxiety.…”
Section: Meta Coachingmentioning
confidence: 99%
See 2 more Smart Citations